The Problem of ‘Open Price Term’ in Contracts of Sale of Goods in Iran and under the United Nations Convention on Contracts for the International Sale of Goods - Akrami, Farzaneh; Shaik Ahmad Yu, Sakina; Mohamed Isa, Suzanna (International Journal of Engineering and Technology, 2018)
This is an undeniable fact is that incomprehensible or restricted rules cause problems for merchants as suppliers. This is more perceptible through domestic rules of the countries. However, international businessmen are also affected by existing conflicts in the international regulations. The concept of â€˜open price termâ€™ in contracts for the sale of goods is one of the best samples for developments in the worldâ€™s trade. However, regarding the open price term, the Iranian law has yet to adopt this vital phenomenon. On the other hand, if Iranian legislator aims to impose open price rules in the regulations, provisions of an international set of rules seem to be a useful model for such regulations as they are more common and have the capacity of being applied in the contracts made by parties from all over the world. As such, the United Nations Convention on Contracts for the International Sale of Goods (CISG), as an international set of rules containing open price rules is chosen in this paper to be studied as a model for such regulations. However, respective Article in CISG consists of some shortcoming as well. Thus, Adopting the doctrinal research method, in this paper aims to highlight the importance of adopting new rules for new methods of transaction and the necessity of amendments on existing rules.Â Â